2015
DOI: 10.1002/14651858.cd010017.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF agents for paediatric psoriasis

Abstract: Cochrane Database of Systematic Reviews Index (CDLQI), and adverse e ects. Our secondary outcomes included the proportion of participants achieving PASI 50 and the Physician's Global Assessment (PGA). Main results We included one study with 211 participants (median age 13 years), in which etanercept (dosage ranged from 0.8 to 50 mg per kilogram of body weight) was compared to placebo. Follow-up was over a 48-week period. At week 12, 57% versus 11% who received etanercept or placebo, respectively, achieved the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 58 publications
0
16
0
1
Order By: Relevance
“…19 The paucity of data on this topic was highlighted by a systematic Cochrane review up to July 2015 on the use of anti-TNFa agents in paediatric psoriasis, and the review found only one randomised controlled trial with a high risk of publication bias. 20 Of all the currently available biological agents, etanercept is the agent for which there are most data concerning its efficacy and safety in paediatric psoriasis. A double-blind, randomised, controlled trial conducted over 264 weeks comparing etanercept 0.8 mg/kg weekly with placebo in 211 patients aged 4-17 years with moderate-to-severe plaque psoriasis found significant superiority in favour of etanercept at weeks 12 and 96, (P < 0.001), with no significant adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The paucity of data on this topic was highlighted by a systematic Cochrane review up to July 2015 on the use of anti-TNFa agents in paediatric psoriasis, and the review found only one randomised controlled trial with a high risk of publication bias. 20 Of all the currently available biological agents, etanercept is the agent for which there are most data concerning its efficacy and safety in paediatric psoriasis. A double-blind, randomised, controlled trial conducted over 264 weeks comparing etanercept 0.8 mg/kg weekly with placebo in 211 patients aged 4-17 years with moderate-to-severe plaque psoriasis found significant superiority in favour of etanercept at weeks 12 and 96, (P < 0.001), with no significant adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Service de Dermatologie, Centre Hospitalier Universitaire de Brest, Brest, France 11 Service de Dermatologie, Centre Hospitalier Universitaire Pontchaillou, Universit e de Rennes, Rennes, France 12 Service de Dermatologie, V en er eologie et Canc erologie Cutan ee, Hôpital de la Timone, Assistance-publique-Hôpitaux de Marseille, Marseille, France 13 Service de P ediatrie, Hôpital Femme-M ere-Enfant, Hospices Civils de Lyon, Bron, France 14 Service de Dermatologie, Hôpital Archet 2, ESPIC CHU-Lenval, Nice, France 15 Service de P ediatrie G en erale, Hôpital Robert Debr e, Assistance Publique-Hôpitaux de Paris, Paris, France 16 Service de Dermatologie, Hôpital Sud, Amiens, France 17 Service de Rhumatologie P ediatrique, Hôpital Femme-M ere-Enfant, Hospices Civils de Lyon, Bron, France 18 Service de Dermatologie, Centre Hospitalier de Cornuaille, Quimper, France 19 Service de Dermatologie, Unit e de Dermatologie P ediatrique, Centre Hospitalier Universitaire de Tours, Universit e de Tours, Tours, France 20 Service de Rhumatologie P ediatrique, Centre Hospitalier Universitaire Bicêtre, Universit e Paris Sud-Saclay, UVSQ, Assistance Publique-Hôpitaux de Paris HP, Le Kremlin Bicêtre, France 21 Service de Dermatologie, Hôpital d'Instruction des Arm ees B egin, Saint Mand e, France 22 Service de Dermatologie, Hôpital de Niort, Niort, France 23 Service de Dermatologie, Centre Hospitalier Universitaire Charles-Nicolle, Rouen, France 24 Service de Dermatologie, Hôpital d'Auxerre, Auxerre, France 25 Service de Dermatologie, Centre Hospitalier Universitaire d'Angers, Angers, France 26 Service…”
unclassified
“…Apart from a dearth of meta-analyses and reviews on IFIs associated with the use of TNFα inhibitors among children and adolescents, 6 a considerable number of studies on pediatric patient populations receiving TNFα inhibitors reported no IFIs. [53][54][55][56][57][58][59][60][61][62][63][64][65] A larger study that included both adults and children that were treated with IFX in combination with other immunosuppressants and/ or steroids for CD showed an acceptable safety profile, although fungal infections were observed in 4% (n=21) of the patients following the first course of treatment. Age at first IFX dose, gender, disease duration and -extent were not associated with infectious adverse events.…”
Section: Risk For Invasive Fungal Infections In Childrenmentioning
confidence: 99%
“…(85,203) #21 (adolescen* or baby or babies or child or children or boy or boys or girl or girls or infant* or infanc* or juvenile* or paediatric or pediatric or preschooler* or schoolboy* or schoolgirl* or schoolchild* or teens or teenage* or toddler* or youth or youths or "young people" or "young person" or "young persons") (193,591) #22 #18 or #19 or #20 or #21 (193,591) #23 #17 and #22 (89) #24 #17 and #22 in Cochrane Reviews (Reviews and Protocols) (15) #25 #17 and #22 in Trials ( Records retrieved: 20.…”
Section: #13 21 #12 and #11mentioning
confidence: 99%